2016
DOI: 10.1159/000443040
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Derived CCL2 is Associated with M1 Activation and Recruitment of Cultured Microglial Cells

Abstract: Background/Aims: Microglia are an essential player in central nervous system inflammation. Recent studies have demonstrated that the astrocytic chemokine, CCL2, is associated with microglial activation in vivo. However, CCL2-induced microglial activation has not yet been studied in vitro. The purpose of the current study was to understand the role of astrocyte-derived CCL2 in microglial activation and to elucidate the underlying mechanism(s). Methods: Primary astrocytes were pre-treated with CCL2 siRNA and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 28 publications
5
51
0
Order By: Relevance
“…A further mechanism elucidated by this study is that Ccl2 induces macrophage polarization to the M1 phenotype through its receptor, Ccr2. The Ccl2/Ccr2 pathway has been reported to skew macrophage polarization at the transcriptomic and functional level in human and mouse macrophages (46)(47)(48)(49). Our studies here provide evidence that Ccl2 can induce Ccr2-dependent expression of M1-associated genes, but not M2-associated genes, and further suggested that the Ccl2/Ccr2 pathway may be associated with M1 macrophage polarization.…”
Section: Discussionsupporting
confidence: 62%
“…A further mechanism elucidated by this study is that Ccl2 induces macrophage polarization to the M1 phenotype through its receptor, Ccr2. The Ccl2/Ccr2 pathway has been reported to skew macrophage polarization at the transcriptomic and functional level in human and mouse macrophages (46)(47)(48)(49). Our studies here provide evidence that Ccl2 can induce Ccr2-dependent expression of M1-associated genes, but not M2-associated genes, and further suggested that the Ccl2/Ccr2 pathway may be associated with M1 macrophage polarization.…”
Section: Discussionsupporting
confidence: 62%
“…A similar role for astrocytes has been theorized in the brain metastatic microenvironment but remains largely unexplored 54 . Here, we establish that melanoma-secreted Aβ directly suppresses astrocyte secretion of several cytokines that recruit and activate microglia, such as CCL2, a potent chemoattractant that polarizes microglia to a pro-inflammatory, anti-tumorigenic M1 phenotype 41 . Furthermore, we demonstrate that melanoma-secreted Aβ inhibits microglial phagocytosis of melanoma cells.…”
Section: Discussionmentioning
confidence: 85%
“…Several of the identified astrocyte-secreted cytokines have documented roles in microglial chemotaxis 40 , activation 31 , and M1 polarization 41 . We therefore sought to examine the effect of melanoma-secreted Aβ on the recruitment of microglia to the metastatic site.…”
Section: Mainmentioning
confidence: 99%
“…In an in vitro study, CCL2 released from primary astrocytes contributed to M1 microglial polarization 191 . In mice with collagenase-induced ICH, a lack of CCL2 or CCR2 decreased the haematoma volume early after collagenase-induced ICH but resulted in delayed recovery from ICH 112 ; these changes correlated with decreases in microglial activation and iNOS expression 112 .…”
Section: Microglial Interactions With Other Cellsmentioning
confidence: 99%